Hollowed-out anchor with HA coating sprayed on surface and preparation method of hollowed-out anchor

By spraying HA coating on the surface of the hollow anchor, the problems of unstable anchor positioning effect and poor postoperative healing effect are solved, and better bone integration and anchor stability are achieved.

CN119455140APending Publication Date: 2025-02-18BEIJING CHUNLIZHENGDA MEDICAL INSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411182402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The positioning effect of existing anchors after implantation is unstable, making it difficult to ensure the postoperative healing effect, and cannot effectively promote the differentiation and osteointegration of osteoblasts.

Method used

The hollow anchor made of PEEK CF material is used and a dense HA coating is sprayed on its surface, and the coating is formed by vacuum plasma spraying.

Benefits of technology

Improves the biocompatibility and bone conductivity of anchors, promotes new bone growth and bone integration, enhances the ability of anchors to bind bone tissue, reduces the risk of shedding, and improves the mechanical properties and stability of anchors. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455140A_ABST
    Figure CN119455140A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical instruments, and particularly discloses a hollow anchor with the surface sprayed with an HA coating and a preparation method of the hollow anchor. The hollow anchor nail with the surface sprayed with the HA coating comprises a nail body made of PEEK CF materials, and the nail body is of a hollow structure. Wherein a compact HA coating is formed on the nail body. The preparation method of the hollow anchor with the HA coating sprayed on the surface comprises the following steps: preparing the anchor body made of a PEEK CF material; and spraying hydroxyapatite powder on the periphery of the nail body by adopting a vacuum plasma spraying method so as to form a compact HA coating. Therefore, the problems that the anchor positioning effect is not stable, and the postoperative healing effect is difficult to guarantee are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical devices, and in particular to a hollow anchor nail with a surface sprayed with HA coating and a preparation method thereof. Background Art

[0002] In the prior art, the produced anchor nail with wire is not hollowed out, such as Figure 1 and Figure 2 As shown. The existing anchor can achieve the effect of surface bone ingrowth when implanted, but after implantation, the anchor will generate stress on the bone channel, destroy the bone channel or reduce the holding force of the bone channel, making it difficult to ensure the stability of the anchor's locking effect on the bone. In addition, since the current anchor cannot promote the differentiation of osteoblasts, the bone integration effect is poor, which affects the patient's postoperative treatment effect.

[0003] Therefore, in view of the problem that the anchor positioning effect is unstable and it is difficult to ensure the postoperative healing effect, a more reasonable technical solution needs to be proposed to solve the current technical problems. Summary of the invention

[0004] The purpose of the present invention is to provide a hollow anchor with a surface sprayed with HA coating and a preparation method thereof, so as to solve the problem that the positioning effect of the anchor is unstable and it is difficult to ensure the postoperative healing effect.

[0005] In order to achieve the above-mentioned object, the present invention provides a hollow anchor nail with a surface sprayed with HA coating, comprising a nail body made of PEEK CF material, wherein the nail body has a hollow structure; wherein a dense HA coating is formed on the nail body.

[0006] In one possible design, the thickness of the HA coating is 30-150 μm.

[0007] In a possible design, the nail body includes a main body and a threaded portion, the main body is provided with a groove, the groove extends along the length direction of the main body, and the groove penetrates the main body in a radial direction; the threaded portion is spirally arranged along the outer circumference of the main body; wherein the exposed area of ​​the groove is formed as the hollow structure.

[0008] In a possible design, the groove is located at the center of the main body to separate the main body into two symmetrical parts.

[0009] In a possible design, the thread lead angle of the threaded portion is 18° to 40°.

[0010] In a possible design, the diameter of the main body is D, and the groove has a first width and a second width in a horizontal plane, wherein the first width is M1, M1=D, and the second width is M2, D / 2<M2<2D / 3.

[0011] In a possible design, the top surface of the groove is formed as a curved surface.

[0012] A method for preparing a hollow anchor nail with a surface sprayed with HA coating, comprising the following steps:

[0013] Preparing a nail body made of PEEK CF material, wherein the nail body has a hollow structure;

[0014] Hydroxyapatite powder is sprayed on the periphery of the nail body by vacuum plasma spraying to form a dense HA coating.

[0015] In one possible design, the vacuum plasma spraying method includes the following steps:

[0016] In a low-pressure inert atmosphere, the powder material is heated by a heat source generated by plasma; wherein the low-pressure inert atmosphere includes a primary gas and a secondary gas, wherein the primary gas is argon and the secondary gas is helium;

[0017] Heating the powder material to a molten or semi-molten state;

[0018] injecting the heated powder material into the plasma flame;

[0019] The high-temperature powder is sprayed out quickly so that it is evenly attached to the periphery of the nail body to obtain a HA coating.

[0020] In a possible design, the spraying parameters in the vacuum plasma spraying method are:

[0021] Current: 500A-1000A;

[0022] Voltage: 36V-48V;

[0023] Power: 32KW-46KW;

[0024] Main gas: argon, 0-60l / min;

[0025] Secondary gas: helium, 0-40l / min;

[0026] Spraying distance: 200mm-350mm.

[0027] PEEK CF material, full name Carbon Fiber Reinforced Polyetheretherketone (PEEK), is a high-performance composite material composed of carbon fiber (CF) and polyetheretherketone (PEEK). The nail body made of this material not only has excellent biocompatibility and mechanical properties, and can be implanted in the human body for a long time without causing rejection, but also has good strength and rigidity, which helps it to be stably implanted in the bone canal and avoid damage to the bone canal. HA (hydroxyapatite) coating has excellent biocompatibility and osteoconductivity, can promote new bone growth, and tightly integrate with bone tissue.

[0028] Based on the hollow structure of the nail body, the mass of the implant can be reduced while maintaining sufficient mechanical strength. The hollow structure also helps to improve the elastic modulus of the material, making it closer to the cortical bone of the human body, which is conducive to stimulating bone regeneration. In addition, the hollow structure can provide a larger space, allowing more bone tissue to grow in and accelerate the repair of the wound. A dense HA coating is coated on the outer surface of the nail body. This coating not only improves the biocompatibility of the anchor, but also enhances its ability to combine with bone tissue, reducing the risk of falling off during use.

[0029] The vacuum plasma spraying method can form a dense HA coating, which can effectively prevent the coating from falling off and cracking. At the same time, it also makes the HA coating have good biocompatibility, can form chemical bonds with bone tissue, promote bone integration and bone regeneration, and can reduce the wear and particle shedding of the anchor during use.

[0030] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0032] Figure 1 It is a structural schematic diagram of the prior art product 1 mentioned in the background technology;

[0033] Figure 2 It is a structural schematic diagram of the prior art product 2 mentioned in the background technology;

[0034] Figure 3 It is a schematic structural diagram of a screw body in a hollow anchor with a surface sprayed with HA coating provided by the present invention in one embodiment;

[0035] Figure 4It is a schematic diagram of the cross-sectional structure of a screw body in a hollow anchor with a surface sprayed with HA coating provided by the present invention in one embodiment;

[0036] Figure 5 yes Figure 4 A schematic diagram of the enlarged structure of part A;

[0037] Figure 6 It is a schematic diagram of the bottom-up structure of a hollow anchor with a surface sprayed with HA coating provided by the present invention in one embodiment.

[0038] Description of Reference Numerals

[0039] 1-nail body, 11-main body, 12-threaded portion, 2-groove, 21-curved surface. DETAILED DESCRIPTION

[0040] The specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings.

[0041] According to the first aspect of the present disclosure, a hollow anchor with a surface sprayed with HA coating is provided, which can be stably implanted into the bone canal to avoid damage to the bone canal, and is beneficial to promoting the recovery of the fracture site. Figures 1 to 6 One specific embodiment is shown.

[0042] See also Figures 1 to 6 As shown, the hollow anchor nail with HA coating sprayed on the surface includes a nail body 1 made of PEEK CF material, and the nail body 1 has a hollow structure; wherein a dense HA coating is formed on the nail body 1.

[0043] PEEK CF material, whose full name is Carbon Fiber Reinforced Polyetheretherketone, is a high-performance composite material composed of carbon fiber (CF) and polyetheretherketone (PEEK). The nail body 1 made of this material not only has excellent biocompatibility and mechanical properties, and can be implanted in the human body for a long time without causing rejection, but also has good strength and rigidity, thereby helping it to be stably implanted in the bone canal and avoid damage to the bone canal. The HA (hydroxyapatite) coating has excellent biocompatibility and osteoconductivity, can promote new bone growth, and tightly integrate with bone tissue.

[0044] Based on the hollow structure of the nail body 1, the mass of the implant can be reduced while maintaining sufficient mechanical strength. The hollow structure also helps to improve the elastic modulus of the material, making it closer to the cortical bone of the human body, which is conducive to stimulating bone regeneration. In addition, the hollow structure can provide a larger space, allowing more bone tissue to grow in and accelerate the repair of the wound. A dense HA coating is coated on the outer surface of the nail body 1. This coating not only improves the biocompatibility of the anchor, but also enhances its ability to combine with bone tissue, reducing the risk of falling off during use.

[0045] In one embodiment provided by the present disclosure, the thickness of the HA coating is 30-150 μm, which ensures that the coating has certain biological activity and mechanical strength, and can initially meet the requirements of integration with bone tissue. In addition, it can provide sufficient biologically active surface to promote the attachment and growth of bone cells on the coating surface, thereby accelerating the bone integration process.

[0046] In practical applications, the choice of coating thickness can be adjusted according to the specific use environment and surgical requirements. For example, in application scenarios that require higher bioactivity, the coating thickness can be appropriately increased; while in application scenarios with strict requirements on weight and rigidity, the coating thickness needs to be controlled within a lower range.

[0047] In an embodiment provided by the present disclosure, the nail body 1 includes a main body 11 and a threaded portion 12. The main body 11 is provided with a groove 2, which extends along the length direction of the main body 11 and penetrates the main body 11 in the radial direction; the threaded portion 12 is spirally arranged along the outer circumference of the main body 11, so that the nail body 1 can be screwed into bones or other hard tissues to provide a firm fixing effect. The exposed area of ​​the groove 2 is formed as a hollow structure.

[0048] The main body 11 is the main part of the nail body 1, bearing most of the structural strength and stability. The groove 2 extending along the length of the main body 11 can significantly reduce the overall weight of the nail body 1 and reduce the burden of the implant on the surrounding tissues. At the same time, it is also beneficial to increase blood flow around the implant and promote the growth and repair of bones and tissues. In addition, the presence of the groove 2 increases the contact area between the nail body 1 and the surrounding tissues, which helps to enhance the stability and biocompatibility of the implant.

[0049] The presence of the groove 2 makes the nail body 1 no longer solid in this area, but forms a grid or window pane-like structure, which can further reduce the weight and may provide additional biological advantages, such as better cell migration and nutrient exchange.

[0050] Furthermore, the groove 2 is located at the center of the main body 11 to separate the main body 11 into two symmetrical parts. The design of the central groove 2 makes the main body 11 highly symmetrical in structure, which not only makes the nail body 1 more harmonious visually, but also ensures its mechanical balance. After implantation in the body, this balance helps to reduce the risk of breakage or loosening due to stress concentration. When the nail body 1 is subjected to external force, the symmetrical structural design enables the force to be evenly distributed to various parts of the nail body 1, which helps to improve the overall strength and stability of the nail body 1 and ensure that it can maintain good performance during long-term use. In addition, the design of the central groove 2 can also increase the contact area between the nail body 1 and the surrounding tissues, which helps to enhance the biocompatibility of the nail body 1 and promote the attachment and growth of cells on the surface of the nail body 1, thereby accelerating the repair process of bones and tissues.

[0051] The groove 2 is located in the center, which plays a role in reducing the weight of the nail body 1. For medical devices that need to be implanted in the body, it can reduce the burden on surrounding tissues, reduce the patient's discomfort, and help promote a faster recovery process.

[0052] Furthermore, the thread lead angle of the threaded portion 12 is 18° to 40°. The thread lead angle is the angle between the thread axis and the tangent of the helix at the mid-diameter of the thread, which determines the inclination of the thread and the shape of the helix. Selecting the thread lead angle can ensure that there is sufficient contact area between the threaded portion 12 and the bone tissue. A larger contact area is conducive to dispersing stress, reducing damage to bone tissue, and improving the stability of the anchor.

[0053] The appropriate thread lead angle can increase the friction between the threaded portion 12 and the bone tissue, making it difficult for the anchor to slip during implantation and maintaining a stable fixation effect in the body, which is of great significance for promoting bone healing and preventing the anchor from loosening.

[0054] The choice of thread lead angle also directly affects the size and direction of the implant force. Within this range, a balance point can be found so that the implant force can overcome the resistance of the bone tissue without causing excessive damage to the surrounding tissue.

[0055] In this regard, those skilled in the art can set the thread lead angle of the threaded portion 12 to 18° to 40° according to actual needs, which helps to ensure the stability and reliability of the anchor in clinical applications and provide patients with better treatment effects and rehabilitation experience.

[0056] In the present disclosure, the diameter of the main body 11 is D, and the groove 2 has a first width and a second width in a horizontal plane, wherein the first width is M1, M1=D, and the second width is M2, D / 2<M2<2D / 3.

[0057] The diameter D of the main body 11 is one of the basic dimensions of the anchor, and the first width M1 of the groove 2 is set to be equal to the diameter D of the main body 11, that is, M1=D. This design allows the groove 2 to be aligned with the edge of the main body 11 on one side of the horizontal plane, forming a smooth transition, which helps to reduce stress concentration, improve the fatigue strength of the anchor, and reduce the risk of damage to surrounding tissues during implantation.

[0058] The second width M2 of the groove 2 is set within a specific range, i.e., D / 2<M2<2D / 3, which not only ensures that the groove 2 has a certain width, thereby increasing the contact area between the anchor and the bone tissue, thereby dispersing stress, reducing damage to the bone tissue, and improving the stability of the anchor. In this way, not only the width of the groove 2 is limited, but also it is prevented from being too wide and weakening the structural strength of the main body 11. At the same time, this width range also helps to maintain the geometric shape and dimensional stability of the groove 2, ensuring that the groove 2 can correctly interact with the bone tissue during the implantation process.

[0059] Through the reasonable design of groove 2, the contact area between the anchor and the bone tissue is increased, thereby improving the stability of the anchor in the body. This helps to reduce the risk of the anchor loosening or falling off, improve the success rate of the operation and the quality of patient recovery. The smooth transition and appropriate contact area design help reduce the risk of damage to surrounding tissues during the implantation process, which helps to reduce the incidence of postoperative complications and speed up the patient's recovery.

[0060] Specifically, the top surface of the groove 2 is formed as a curved surface 21. The curved surface 21 is designed to effectively disperse the stress acting on the top surface of the groove 2. Compared with a flat surface, the curved surface 21 has better flexibility and adaptability, and can better disperse and absorb stress when subjected to external force, thereby reducing the risk of stress concentration, which is of great significance for improving the fatigue strength of the anchor and extending its service life.

[0061] The design of the curved surface 21 makes the contact between the top surface of the groove 2 and the bone tissue more intimate and uniform. When the anchor is implanted in the body, the curved surface 21 can better adapt to the surface shape of the bone tissue and reduce the generation of gaps and voids. This intimate contact helps to increase the friction between the anchor and the bone tissue, improve the stability of the anchor, and promote the growth and repair of bone tissue.

[0062] The curved surface 21 design also helps to reduce the risk of damage to surrounding tissues during the implantation of the anchor. Since the curved surface 21 has better adaptability and flexibility, it can reduce the pressure and friction on the surrounding tissues during the implantation process, thereby reducing the incidence of tissue damage and inflammatory response.

[0063] According to a second aspect of the present disclosure, a method for preparing a hollow anchor with a surface sprayed with HA coating is provided.

[0064] The preparation method of the hollow anchor nail with HA coating sprayed on the surface comprises the following steps: preparing a nail body 1 made of PEEK CF material, wherein the nail body 1 has a hollow structure; and spraying hydroxyapatite powder on the periphery of the nail body 1 by vacuum plasma spraying to form a dense HA coating.

[0065] PEEK CF (polyetheretherketone carbon fiber composite material) is selected as the base material of the nail body 1, so that the nail body 1 has excellent biocompatibility, mechanical properties and chemical stability. The nail body 1 is made into a hollow structure, which can improve the biocompatibility and bone integration ability of the anchor nail.

[0066] Hydroxyapatite powder is sprayed on the periphery of the nail body 1 by vacuum plasma spraying. In the vacuum plasma spraying equipment, a low-pressure inert atmosphere (such as an argon or helium environment) is first created to reduce the influence of oxygen and other impurities in the air on the plasma and coating quality. Hydroxyapatite (HA) powder is used as a spraying material and is heated and melted by a high-temperature plasma flame generated by a plasma generator. In this process, the high temperature of the plasma causes the HA powder to melt rapidly and form molten droplets. The molten HA droplets are sprayed at high speed to the periphery of the nail body 1, and are rapidly cooled and solidified when they hit the surface of the substrate to form a dense HA coating. Due to the use of vacuum plasma spraying, a strong chemical bond and mechanical bite can be ensured between the coating and the substrate, thereby improving the adhesion and durability of the coating.

[0067] HA is one of the main inorganic components of human bones and teeth, so it has excellent biocompatibility. Spraying HA coating on the surface of anchors can promote the growth and attachment of bone cells, improve bone integration ability, enable anchors to withstand complex biomechanical environments, and maintain good long-term stability. HA coatings can maintain stable chemical properties in the human body and are not easy to react with other substances, which helps reduce the occurrence of inflammatory reactions and rejection reactions and improve the safety and effectiveness of implants.

[0068] After the nail body 1 is prepared, hydroxyapatite (HA) powder is sprayed on its periphery by vacuum plasma spraying. Vacuum plasma spraying is an advanced surface treatment technology that uses the high temperature and high speed characteristics of plasma to heat the powder material to a molten or semi-molten state and spray it onto the surface of the substrate to form a coating. It has the advantages of good coating quality, high bonding strength, and strong process controllability.

[0069] Before spraying, the surface of the nail body 1 needs to be cleaned and roughened to improve the adhesion and bonding strength of the coating.

[0070] The nail body 1 is placed in a vacuum chamber, an inert gas (such as argon) is introduced as a protective gas, and plasma is generated. At the same time, hydroxyapatite powder is fed into the plasma jet, heated to a molten or semi-molten state, and sprayed onto the surface of the nail body 1.

[0071] The coating rapidly cools and solidifies on the substrate surface to form a dense HA coating.

[0072] The vacuum plasma spraying method can form a dense HA coating, which can effectively prevent the coating from falling off and cracking. At the same time, it also makes the HA coating have good biocompatibility, can form chemical bonds with bone tissue, promote bone integration and bone regeneration, and can reduce the wear and particle shedding of the anchor during use.

[0073] When preparing the hollow rivet disclosed in the present invention, it is necessary to form a plasma arc by adjusting the gas flow rate of argon and helium and the current of the spray gun under low pressure, and control the angle, moving speed, spraying distance, etc. of the spray gun by the machine arm, and inject HA powder into the plasma flame flow by using a powder feeding device. It is accelerated and melted during flight, and finally sprayed onto the pretreated PEEK CF anchor to form a firmly adhered HA coating.

[0074] Under vacuum conditions, the HA powder particles and air flow speed are very high, and the HA coating formed is very dense, so the bonding strength with the substrate is high. The working gas is an inert gas, which protects the substrate and powder from oxidation, and there are fewer impurities in the coating. The spray gun and the substrate move at a high speed relative to each other, so that the matrix structure does not change, and the shape and performance of the substrate will not be affected by heat.

[0075] Specifically, the vacuum plasma spraying method includes the following steps: in a low-pressure inert atmosphere, heating the powder material using the heat source generated by plasma; wherein the low-pressure inert atmosphere includes a primary gas and a secondary gas, wherein the primary gas is argon and the secondary gas is helium; heating the powder material to a molten or semi-molten state; injecting the heated powder material into a plasma flame flow; rapidly spraying the high-temperature powder so that it is evenly attached to the outer periphery of the nail body 1 to obtain a HA coating.

[0076] Create a low pressure environment inside the vacuum chamber to reduce the influence of air on plasma and coating quality.

[0077] The primary gas (argon) and secondary gas (helium) are introduced as inert atmospheres. Argon is selected as the primary gas because of its high chemical stability and low reaction with other elements to protect the plasma jet and coating surface. Helium, as the secondary gas, may be used to adjust the electrical conductivity, thermal conductivity or other physical properties of the atmosphere to optimize the performance of the plasma.

[0078] Plasma is generated by exciting in an inert atmosphere using electrical energy or other energy sources (such as radio frequency, microwave, etc.). Plasma is a highly ionized gas containing a large number of free electrons, ions and neutral particles with extremely high temperature and energy density.

[0079] Hydroxyapatite (HA) powder is fed into the heat source area of ​​the plasma. The high temperature of the plasma (up to thousands of degrees Celsius) heats the powder material to a molten or semi-molten state. In this process, the surface of the powder particles is rapidly heated and melted, but the inside may still remain solid or semi-solid.

[0080] The heated powder material is injected into the plasma flame through a specific nozzle or device. The plasma flame is a high-temperature and high-speed airflow generated by plasma, which can accelerate the powder particles and spray them onto the surface of the substrate (i.e., the nail body 1).

[0081] When the high-speed sprayed powder particles hit the surface of the nail body 1, due to the dual effects of high temperature and high speed, they can quickly react physically and chemically with the substrate surface to form a strong bond. At the same time, the coating quickly cools and solidifies on the substrate surface to form a dense HA coating.

[0082] By adjusting the plasma parameters (such as power, gas flow, nozzle position, etc.) and the powder supply rate and injection angle, it is possible to ensure that the high-temperature powder is evenly attached to the periphery of the nail body 1 to form a uniform and dense HA coating.

[0083] Vacuum plasma spraying can form a dense and non-porous HA coating, which effectively prevents the coating from falling off and cracking. A strong chemical bond and mechanical bite are formed between the coating and the substrate, which improves the bonding strength of the coating. The HA coating has good biocompatibility and can promote the integration between bone tissue and anchors. The high hardness and wear resistance of the coating can reduce the wear and particle shedding of the anchor during use.

[0084] Specifically, the spraying parameters in the vacuum plasma spraying method are: current: 500A-1000A; voltage: 36V-48V; power: 32KW-46KW; main gas: argon, 0-60l / min; secondary gas: helium, 0-40l / min; spraying distance: 200mm-350mm.

[0085] Electric current is one of the main energy sources for generating plasma. Higher current can generate more intense plasma, improve heating efficiency and melting speed of powder. In vacuum plasma spraying process, voltage mainly affects the formation and maintenance of plasma. Appropriate voltage can ensure the stability and uniformity of plasma, which is beneficial to the heating of powder and the formation of coating. However, too high voltage may also lead to unstable plasma discharge and even cause adverse phenomena such as arc discharge.

[0086] Power is the product of current and voltage, and reflects the total energy output of the plasma. In vacuum plasma spraying, the power directly affects the heating rate of the powder and the rate of coating formation. Higher power can improve spraying efficiency, but it may also cause problems such as overheating, oxidation or burning of the coating. Therefore, when selecting power, it is necessary to adjust it according to the specific material and process requirements.

[0087] Argon, as the main gas, plays a role in protecting the plasma jet and coating surface in vacuum plasma spraying. Appropriate main gas flow rate can ensure the stability of plasma and the uniformity of coating. However, too high main gas flow rate may also cause plasma dilution and reduce heating efficiency. Therefore, it is necessary to adjust the main gas flow rate according to actual conditions.

[0088] Helium as a secondary gas may be used to adjust the conductivity, thermal conductivity or other physical properties of the atmosphere in vacuum plasma spraying. The setting of the secondary gas flow rate depends on the specific process requirements and equipment performance. In some cases, the secondary gas may not be necessary or only a small flow rate is required.

[0089] The spraying distance refers to the distance between the nozzle and the substrate surface, which directly affects the spraying speed of the powder particles and the energy when they hit the substrate. The appropriate spraying distance can ensure that the powder particles are evenly attached to the substrate surface and form a dense coating. However, a spraying distance that is too close may cause excessive melting or burning of the powder particles; a spraying distance that is too far may reduce the adhesion and uniformity of the coating.

[0090] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A hollow anchor with HA coating sprayed on the surface, characterized in that: It comprises a nail body made of PEEK CF material, wherein the nail body has a hollow structure; wherein a dense HA coating is formed on the nail body.

2. The hollow anchor with HA coating sprayed on the surface according to claim 1, characterized in that: The thickness of the HA coating is 30-150 μm.

3. The hollow anchor with HA coating sprayed on the surface according to claim 1, characterized in that: The nail body includes a main body and a threaded portion, the main body is provided with a groove, the groove extends along the length direction of the main body, and the groove penetrates the main body in a radial direction; the threaded portion is spirally arranged along the outer circumference of the main body; wherein the exposed area of ​​the groove forms the hollow structure.

4. The hollow anchor with HA coating sprayed on the surface according to claim 3, characterized in that: The groove is located at the center of the main body to separate the main body into two symmetrical parts.

5. The hollow anchor with HA coating sprayed on the surface according to claim 3, characterized in that: The thread lead angle of the threaded portion is 18° to 40°.

6. The hollow anchor with HA coating sprayed on the surface according to claim 3, characterized in that: The diameter of the main body is D, and the groove has a first width and a second width in a horizontal plane, wherein the first width is M1, M1=D, and the second width is M2, D / 2<M2<2D / 3.

7. The hollow anchor with HA coating sprayed on the surface according to claim 3, characterized in that: The top surface of the groove is formed as a curved surface.

8. A method for preparing a hollow anchor with a surface sprayed with HA coating as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Preparing a nail body made of PEEK CF material, wherein the nail body has a hollow structure; Hydroxyapatite powder is sprayed on the periphery of the nail body by vacuum plasma spraying to form a dense HA coating.

9. The method for preparing a hollow anchor with a surface sprayed with HA coating according to claim 8, characterized in that: The vacuum plasma spraying method comprises the following steps: In a low-pressure inert atmosphere, the powder material is heated by a heat source generated by plasma; wherein the low-pressure inert atmosphere includes a primary gas and a secondary gas, wherein the primary gas is argon and the secondary gas is helium; Heating the powder material to a molten or semi-molten state; injecting the heated powder material into the plasma flame; The high-temperature powder is sprayed out quickly so that it is evenly attached to the periphery of the nail body to obtain a HA coating.

10. The method for preparing a hollow anchor with a surface sprayed with HA coating according to claim 9, characterized in that: The spraying parameters in the vacuum plasma spraying method are: Current: 500A-1000A; Voltage: 36V-48V; Power: 32KW-46KW; Main gas: argon, 0-60l / min; Secondary gas: helium, 0-40l / min; Spraying distance: 200mm-350mm.